2021
DOI: 10.1093/advances/nmab108
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Links between Diet and Inflammation: Dairy Foods as Case Studies

Abstract: Systemic chronic inflammation may be a contributing factor to many noncommunicable diseases, including diabetes, cardiovascular disease, and obesity. With the rapid rise of these conditions, identifying the causes of and treatment for chronic inflammation is an important research priority, especially with regard to modifiable lifestyle factors such as diet. An emerging body of evidence indicates that consuming certain foods, including dairy foods like milk, cheese, and yogurt, may be linked to a decreased risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 75 publications
(83 reference statements)
1
15
0
Order By: Relevance
“…• Refined grains Low in nutrients and dietary fiber with an inadvertent effect on gut microbiome 103 and oxidative stress 4,84,85 • Fatty meat and fatty meat products Saturated fat from meat has pro-inflammatory effects 39,40 Western diet with high consumption of (processed) meat, refined sugars and processed foods is associated with mortality, 52 chronic disease, 27,43,44,[46][47][48][49] pro-inflammatory microbiome, 50 and allergic disease.…”
Section: Recommended Foods In Age-appropriate Amountsmentioning
confidence: 99%
“…• Refined grains Low in nutrients and dietary fiber with an inadvertent effect on gut microbiome 103 and oxidative stress 4,84,85 • Fatty meat and fatty meat products Saturated fat from meat has pro-inflammatory effects 39,40 Western diet with high consumption of (processed) meat, refined sugars and processed foods is associated with mortality, 52 chronic disease, 27,43,44,[46][47][48][49] pro-inflammatory microbiome, 50 and allergic disease.…”
Section: Recommended Foods In Age-appropriate Amountsmentioning
confidence: 99%
“…In fact, growing attention is being paid to the role of nutrition in the health of the retina and visual impairment. Several studies suggested antioxidant and anti-inflammatory effects of some specific foods [ 40 , 41 ]. The AREDS1 and AREDS2 pieces of research focused on specific nutritional intake and dietary supplements as strategies for preventing and slowing down AMD development.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that an alteration in the balance of dietary omega 3- and omega 6, with a high food intake of omega 6, increases the risk of developing AMD [ 63 ]. The MedDiet has been defined as a longevity determinant thanks to the properties of its components [ 40 , 41 ]. Considerable scientific evidence supports the protective and preventive role of this food pattern against chronic noncommunicable diseases [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is a physiological protective mechanism and a necessary part of healing ( 88 ). Evidence supporting the impact of specific foods on chronic persistent inflammation in the body is limited ( 89 ). Inflammation is useful because it is the result of the body fighting the infection; however, it is adverse because it damages a lot of the healthy cells in the process.…”
Section: Anti-inflammatory Activity Of Mushroomsmentioning
confidence: 99%